Impaired Health-related Quality of Life in Caregivers of Youth Seeking Obesity Treatment - Modi, Avani C. (Oxford University Press, 2009)
Objective To document and identify predictors of caregiver health-related quality of life (HRQOL) in a sample of youth seeking obesity treatment and examine whether it moderates the relation between parent proxy and youth self-report HRQOL. Methods Youth (5–18 years) and their caregivers (N = 120) presenting to a pediatric medical weight management program completed the Pediatric Quality of Life Inventory™ and caregivers completed the Short-Form 36. Results Caregivers were predominantly overweight/obese (90%) and half were African-American. Caregiver HRQOL was lower than “healthy” adults, similar to nontreatment-seeking adults with obesity, and better than treatment-seeking adults with obesity. Caregiver body mass index and socioeconomic status predicted caregiver physical HRQOL. Caregiver age predicted caregiver mental HRQOL. A moderation effect was not detected. Conclusions Given the significant degree of overweight and HRQOL impairment in caregivers of youth seeking obesity treatment, further examination of caregiver functioning in the context of pediatric obesity treatment outcomes is warranted.